Electrochemical triggering of lipid bilayer lift-off oscillation at the electrode interface - Ryzhkov, Nikolay V. (J R Soc Interface, 2019)
In situ studies of transmembrane channels often require a model bioinspired artificial lipid bilayer (LB) decoupled from its underlaying support. Obtaining free-standing lipid membranes is still a challenge. In this study, we suggest an electrochemical approach for LB separation from its solid support via hydroquinone oxidation. Layer-by-layer deposition of polyethylenimine (PEI) and polystyrene sulfonate (PSS) on the gold electrode was performed to obtain a polymeric nanocushion of [PEI/PSS](3)/PEI. The LB was deposited on top of an underlaying polymer support from the dispersion of small unilamellar vesicles due to their electrostatic attraction to the polymer support. Since lipid zwitterions demonstrate pH-dependent charge shifting, the separation distance between the polyelectrolyte support and LB can be adjusted by changing the environmental pH, leading to lipid molecules recharge. The proton generation associated with hydroquinone oxidation was studied using scanning vibrating electrode and scanning ion-selective electrode techniques. Electrochemical impedance spectroscopy is suggested to be a powerful instrument for the in situ observation of processes associated with the LB–solid support interface. Electrochemical spectroscopy highlighted the reversible disappearance of the LB impact on impedance in acidic conditions set by dilute acid addition as well as by electrochemical proton release on the gold electrode due to hydroquinone oxidation.